Technical economic analysis of PV-driven electricity and cold cogeneration systems using particle swarm optimization algorithm. (15th November 2020) - Perrigot, Antoine; Perier-Muzet, Maxime; Ortega, Pascal; Stitou, Driss
Abstract: Three different studies are presented in this paper. As a first step, a Particle Swarm Optimization (PSO) algorithm is used to optimize a prototype of cold/electricity cogeneration designed to be disconnected from the grid and implanted in an insular tropical region where a high need of cold and electricity is required. The electricity is provided by solar photovoltaic panels and the electrical energy in excess is stored in the form of hydrogen thanks to an electrolyzer. When a lack of electricity occurs a fuel cell provides the missing electricity by using the stored hydrogen. An electrically driven heat pump is also used to produce and cover the cold needs. Finally, in order to increase the overall efficiency of this electricity/cold cogeneration system, the low-grade waste heat generated by the different components of the system, mostly the electrolyzer and the fuel cell, is recovered and upgraded by a thermochemical reactor enabling a further cold production. The thermochemical reactor assists the heat pump for the cold supply, decreasing thus the electricity consumption. Such a prototype is intended to be built in Tahiti during the RECIF project. The PSO algorithm has been implemented and results are promising because component's size is reasonable, and the driving strategy is consistent while both demands are always satisfied. In a second study, the same PSO algorithm has been used to perform an analysis and identify a general shape of load profiles for which it become interesting, from an economic point of view, to store electricity into hydrogen instead of electrochemical batteries when the cold production is only handled by a heat pump. This study has shown that the more electricity is consumed at night, the more it is interesting to use hydrogen. Finally, the algorithm has been used to see the evolution of the economic interest when a thermochemical system is added. This study has been carried out considering a storage into hydrogen and an exploitation of the low-grade heat by a thermochemical unit to enable a further cold production. The economic interest of a thermochemical system has not been proven by this study, that is why further considerations must be considered in order to justify its use as ecological impacts for example. Highlights: PSO can be applied on cogeneration systems to size them and find a driving strategy. Hydrogen becomes more interesting than batteries when storage needs are increasing. Thermochemical systems are useful to increase efficiency. Thermochemical systems cost can be compensated if cold consumption occurs at night.